The prevalence of bcl-2, p53, and Ki-67 immunoreactivity in transitional cell bladder carcinomas and their clinicopathologic correlates - Nakopoulou, L.; Vourlakou, C.; Zervas, A.; Tzonou, A.; Gakiopoulou, H; Dimopoulos, M.-A. (Human Pathology, 1998)
The aim of this study was to investigate the expression of bcl-2, p53 oncoproteins, and Ki-67 antigen in a series of transitional cell bladder carcinomas and its relation to the traditional prognostic indicators and patient's survival. One hundred six cases with transitional cell carcinoma (TCC) were examined for detection of bcl-2, p53 proteins, and Ki-67 antigen (MIB1 antibody). Bcl-2 immunohisto-chemical positivity was observed in 52% of TCCs and in 577% of low-grade and 44% of high-grade TCCs. Bcl-2 was also detected in normal urothelium and dysplastic lesions with basal cell expression, showed a significant inverse correlation with overall bcl-2 positivity. The loss of bcl-2 protein expression in higher-stage TCCs was statistically significant (pt = .01). P53 protein was overexpressed in 50% of TCCs and more frequently in invasive and in carcinomas in situ than in superficial TCCs (Pt = .03). In contrast, detection of p53 was not observed in normal and dysplastic urothelium. P53 positivity was related to the degree of differentiation and to the stage of the disease (Pf = .01 and Pt = .03, respectively). Concerning Ki-67 antigen, its expression was found in 57.5% of TCCs. There was a strong overall correlation of Ki-67 with tumor stage (Pt = .002) and grade (Pf = .002). Univariate statistical analysis showed that the expression of p53 and Ki-67 was significantly correlated to poor prognosis (p = .02, P = .02, respectively). On multivariate analysis, none of these markers but only stage and grade were significantly correlated to prognosis (P = .02, respectively). These findings suggest that overexpression of bcl-2 protein may be an early event in tumorigenesis. Tumors with loss of bcl-2 positivity and overexpression of p53 and Ki-67 had an unfavorable prognosis; however, in multivariate analysis, they had no independent prognostic value.
Keywords: Bcl-2; Ki-67; p53; transitional cell carcinoma